Neither abuse, nor neglect: A duty of care perspective on academic integrity - Gedajlovic, Eric; Wielemaker, Martin (Canadian Perspectives on Academic Integrity, 2020)
Approaches and mindsets related to academic integrity are increasingly bifurcating into two polarized camps: one that is characterized by a law-and-order approach and one that prioritizes student experience. The first has been accused of being abusive or insensitive to the stress and anxiety that the approach may cause students, the latter of being neglectful of the need to maintain high standards of academic integrity. This polarization is unhelpful as it hinders thoughtful discussion as well as the formulation of balanced solutions that maintain high standards of academic integrity while also being sensitive to the psycho-emotional needs of students. To address these issues, we propose a duty-of-care perspective, which is based on the principle that as educators, we have a duty-of-care obligation to others and we must therefore act to address academic misconduct, but not without a consideration of the costs and burdens it places on others. Our duty-of-care perspective offers a framework that provides (1) a prosocial motivation and frame of reference for dealing with academic integrity, (2) a guide for developing and assessing alternative courses of action in a balanced and holistic way and, (3) a frame for messaging to stakeholders that we have a duty to act based upon care and shared responsibilities. If we are all in this together, rather than retreating into opposing camps, the duty-of-care perspective unites us around our shared responsibilities.